2016
DOI: 10.1161/atvbaha.116.308339
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Endothelial Dysfunction in Sedentary, Obese Humans Is Mediated by NADPH Oxidase

Abstract: Objective The objectives of this study were to determine the impact of in vivo reactive oxygen species (ROS) on microvascular endothelial function in obese human subjects and to determine the efficacy of an aerobic exercise intervention on alleviating obesity-associated dysfunctionality. Approach and Results Young, sedentary men and women were divided into lean (BMI 18–25; n=14), intermediate (BMI 28–32.5; n=13), and obese (BMI 33–40; n=15) groups. A novel microdialysis technique was utilized to detect eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 53 publications
5
54
0
1
Order By: Relevance
“…With this method, they showed that NADPH oxidase-derived ROS levels were elevated in obese subjects, associated with microvascular endothelial dysfunction as evidenced by impaired acetylcholine-induced blood flow increases. 18 Notably, an 8-week aerobic exercise training normalized both the elevated ROS levels and the microvascular endothelial dysfunction in this study. 18 In striking contrast, the physiological roles of ROS in the regulation of vascular homeostasis have been brought to light.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 47%
See 2 more Smart Citations
“…With this method, they showed that NADPH oxidase-derived ROS levels were elevated in obese subjects, associated with microvascular endothelial dysfunction as evidenced by impaired acetylcholine-induced blood flow increases. 18 Notably, an 8-week aerobic exercise training normalized both the elevated ROS levels and the microvascular endothelial dysfunction in this study. 18 In striking contrast, the physiological roles of ROS in the regulation of vascular homeostasis have been brought to light.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 47%
“…18 Notably, an 8-week aerobic exercise training normalized both the elevated ROS levels and the microvascular endothelial dysfunction in this study. 18 In striking contrast, the physiological roles of ROS in the regulation of vascular homeostasis have been brought to light. 16 Gray et al 19 demonstrated the atheroprotective role of NADPH oxidase 4-derived hydrogen peroxide (H 2 O 2 ) in a diabetic atherosclerosis mouse model.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 47%
See 1 more Smart Citation
“…50 ROS regulates EC biology. 37,[52][53][54][55] However, evidence on thrombosis regulation by EC-derived ROS is limited. Antioxidative treatment inhibits the release of thrombogenic TF from irradiation-and cytokinetreated ECs, indicating a significant role of endothelial ROS in thrombotic regulation.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…These data suggest that exercise and fat accumulation heavily contribute to the regulation of ROS in the vasculature through NOX protein expression in adjacent tissues. 55 …”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%